Pengenalan Teknologi CAD 3D Solidworks dan Pemindai 3D untuk Masyarakat Industri di Purwakarta - fatkur rachmanu; Widodo; Ade Irvan Tauvana; Lukman Nulhakim; Syafrizal; Mokhamad Is Subekti (Yayasan Pemimpin Inovasi Science, 2025)
Technological developments in the industrialized world have encouraged the use of computer-based design technologies, such as Solidworks 3D CAD and 3D scanning, to improve efficiency and innovation in the design and product development process. However, the limited understanding and access to these technologies among the industrial community, especially the new workforce, is a challenge that needs to be overcome. This training aims to introduce Solidworks 3D CAD technology based on the 3D-Experience platform and 3D scanners to 52 participants who are students, private employees, and entrepreneurs. The training methods used included theoretical presentations, tool demonstrations, and evaluation through pre- and post-training quizzes. The results showed an average increase in participants' understanding of 76.3%, with a satisfaction level of 55%. This training proved its success in improving the technological competence of the participants and providing input for future training improvements. This activity is expected to bridge the industry's need for skilled labor and support global competitiveness.